Implementing Collaborative Governance to Realize Substantive Public Services: A Case Study of the Permata Hati Ecotourism Program - Faizul Abror; Hayat Hayat; Septina Dwi Rahmawati (Madani: Jurnal Politik dan Sosial Kemasyarakatan, 2026)
Collaborative-based public service delivery has emerged as a vital approach in fostering sustainable community development, particularly through participatory ecotourism management. This study aims to comprehensively analyze the practice of collaborative governance in realizing public services through the Permata Hati Ecotourism Program in Panglungan Village, Jombang Regency, Indonesia. Employing a qualitative research method with a case study approach, empirical data were gathered through in-depth interviews, participant observations, and document analysis, which were subsequently analyzed using an interactive data analysis model. The theoretical framework relies on the collaborative governance model proposed by Ansell and Gash (2008). The findings reveal four key dimensions: (1) the starting conditions of the program were deeply rooted in local grassroots initiatives driven by severe forest degradation and resource scarcity, which ultimately catalyzed the necessity for multi-actor collaboration; (2) the institutional design is robustly supported by formal legal frameworks (Memorandum of Understanding, Environmental Agency Decrees, and Regent Regulations), inclusive deliberative forums, and transparent communication channels; (3) facilitative leadership is effectively distributed among local community figures (Wagisan), Non-Governmental Organizations (Ecoton), and the local government (Environmental Agency/DLH); and (4) the collaborative process has successfully generated significant 'small wins,' including the ecological restoration of 70 hectares of conservation forest, the preservation of five vital water springs, and the enhancement of the local community's economic well-being. In conclusion, the practice of collaborative governance in this program has been highly adaptive, inclusive, and sustainable. It demonstrates that public service delivery is not merely an administrative procedure, but rather a substantive collective action toward environmental conservation and community empowerment.